1995
DOI: 10.1074/jbc.270.12.6639
|View full text |Cite
|
Sign up to set email alerts
|

Direct Activation of Protein Kinase C by 1α,25-Dihydroxyvitamin D3

Abstract: The key metabolite of vitamin D3, 1 alpha,25-dihydroxyvitamin D3 (1,25-D3), induces rapid cellular responses that constitute a so-called "non-genomic" response. This effect is distinguished from its "classic" genomic role in calcium homeostasis involving the nuclear 1,25-D3 receptor. Evidence is presented that protein kinase C (PKC) is directly activated by 1,25-D3 at physiological concentrations (EC50 = 16 +/- 1 nM). The effect was demonstrable with single PKC-alpha, -gamma, and -epsilon isoform preparations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
109
5

Year Published

1996
1996
2004
2004

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 142 publications
(123 citation statements)
references
References 53 publications
9
109
5
Order By: Relevance
“…It has been demonstrated that 1␣,25(OH) 2 D 3 alone can directly activate PKC and increase VDR phosphorylation. 35,36 PMA was reported to up-regulate VDR mRNA and the VDR protein levels in myeloid cells or non-myeloid cells by activation of PKC. 37,38 Furthermore, it has been suggested that PKC down-regulation rather than activation by bryostatin or PMA plays a role in the differentiation of several cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that 1␣,25(OH) 2 D 3 alone can directly activate PKC and increase VDR phosphorylation. 35,36 PMA was reported to up-regulate VDR mRNA and the VDR protein levels in myeloid cells or non-myeloid cells by activation of PKC. 37,38 Furthermore, it has been suggested that PKC down-regulation rather than activation by bryostatin or PMA plays a role in the differentiation of several cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Table III, the C1A domain bound DiC 8 with a K d of 85 nM, whereas the C1B domain showed no detectable binding. Thus, as was the case with PKC␣ (38,74), the C1A and C1B domains of PKC␦ have opposite affinities for DAG and phorbol ester, i.e. the C1A domain with high affinity for DAG and the C1B domain with high affinity for phorbol ester.…”
Section: Phosphatidylserine (Ps)-specific Membranementioning
confidence: 99%
“…However, in recent studies of activator binding to PKC␣, using the fluorescent phorbol ester sapintoxin D (SAPD), we showed that diacylglycerols and phorbol esters interact with differing affinities with two activator binding sites on the enzyme molecule (34 -36). Furthermore, it was shown that the site with low affinity for phorbol esters binds diacylglycerol with a relatively higher affinity, suggesting that the specificity of this site may differ from the high affinity phorbol ester-binding site (35). Interaction of diacylglycerol with this low affinity phorbol ester-binding site was found to lead to an enhancement in the level of high affinity phorbol ester binding and consequently to a potentiated level of PKC activity.…”
mentioning
confidence: 99%